2010
DOI: 10.1038/ki.2010.250
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus attenuates disease progression in an orthologous mouse model of human autosomal dominant polycystic kidney disease

Abstract: In autosomal dominant polycystic kidney disease (ADPKD), abnormal proliferation of tubular cells drives cyst development and growth. Sirolimus, an inhibitor of the protein kinase mammalian target of rapamycin (mTOR) and a potent anti-proliferative agent, decreases cyst growth in several genetically distinct rodent models of polycystic kidney disease (PKD). We determined here the effect of sirolimus on renal cyst growth in Pkd2WS25/- mice; an ortholog of human ADPKD involving mutation of the Pkd2 gene. In Pkd2W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 42 publications
5
74
0
6
Order By: Relevance
“…Previous studies also showed beneficial effects of rapamycin in two orthologous PKD mouse models. 30,31 High-dose sirolimus (blood level of 22 ng/ml) has been shown to reduce cyst growth in Pkd2 WS25/-mice without improvement of renal function, 31 whereas rapamycin reduced cyst growth and improved renal function in a conditional Pkd1-knockout model. In this model, drug levels in circulation were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed beneficial effects of rapamycin in two orthologous PKD mouse models. 30,31 High-dose sirolimus (blood level of 22 ng/ml) has been shown to reduce cyst growth in Pkd2 WS25/-mice without improvement of renal function, 31 whereas rapamycin reduced cyst growth and improved renal function in a conditional Pkd1-knockout model. In this model, drug levels in circulation were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…93 First shown in the Cy/+ rat model, 94 the efficacy of mTORC1 inhibitors to reduce cyst growth and to ameliorate disease progression was subsequently demonstrated in several animal models of cystic kidney disease, including Pkd1-deficient mice. 90,[95][96][97][98][99][100] Despite these encouraging preclinical data, mTOR inhibitors did not yield the expected benefits in patients with ADPKD. While everolimus slowed cyst growth in ADPKD patients, this inhibition did not translate into an improvement of renal function.…”
Section: Gerd Walzmentioning
confidence: 99%
“…Furthermore, treatment of PKD rodent models with mTOR inhibitors, such as rapamycin, greatly improves the cystic phenotype. [5][6][7][8][9][10][11] Because mTOR inhibitors have already been in clinical use as immunosuppressant drugs, these studies rapidly led to several clinical trials to determine whether they are effective in patients with APDKD. [12][13][14] Unfortunately, although not yet fully conclusive, the results of these trials have been largely disappointing.…”
mentioning
confidence: 99%
“…2 Currently, no treatment for ADPKD is available, and most patients eventually require lifelong dialysis or kidney transplantation. We 3,4 and others [5][6][7][8][9][10][11] have demonstrated that the mammalian target of rapamycin (mTOR) pathway is hyperactivated in PKD rodent models and human ADPKD. Furthermore, treatment of PKD rodent models with mTOR inhibitors, such as rapamycin, greatly improves the cystic phenotype.…”
mentioning
confidence: 99%